African migrations traversing hybrid landscapes - Gintsburg, Sarali 1976-; Breeze, Ruth (Lexington Books, 2024)
"This book explores the hybrid landscapes of African migration and offers new insights into the complexity of migratory movements and migrant experiences associated with the African continent. The methodological approaches within this volume include sociolinguistic analysis, literary analysis, and autoethnography"--
Includes bibliographical references and index
Keywords: Geschichte; Migration; Afrika; African diaspora; Africans / Migrations; African diaspora in literature